The Effect of Store Atmosphere towards Student Purchase Decision - Ilham Prawidi Sakti; Imas Permatasari; Andriansyah Bari (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2023)
This study aims to determine the relationship between store atmosphere (cleanliness, scent, temperature, lighting, and layout) with purchasing decisions in the learning lab of the Politeknik Negeri Sriwijaya Department of Business Administration. The type of this research is descriptive and quantitative. This research uses a sample of 126 respondents through questionnaires. The sample of this study consisted of all customers who made transactions in the learning lab of the Department of Business Administration, Politeknik Negeri Sriwijaya Palembang. This study uses multiple linear regression analysis using SPSS software. The results of this study indicate that the variables of cleanliness, scent, temperature, and layout have a significant influence on purchasing decisions. While the lighting variable has a less significant effect on purchasing decisions. The results of this study can be concluded that store atmosphere has a significant effect on purchase decision at Business Teaching Factory di Politeknik Negeri Sriwijaya, with scent has the strongest effect while lighting has the least effect.